The Influence of Forage Type Provision on the Growth Performance and Body Weight Gain of Rex Rabbits (Oryctolagus cuniculus)): Pengaruh Pemberian Jenis Pakan Hijauan terhadap Pertambahan Bobot Badan Kelinci Rex (Oryctolagus cuniculus) - Rizky Amrullah Chaniago; Nurazizah Ramadhanti; Muhammad Dani; Woki Bilyaro; Arif Rahman Azis (Buletin Peternakan Tropis, 2026)
This study aimed to evaluate the effects of three different forage types on the growth performance of Rex rabbits (Oryctolagus cuniculus), focusing on feed intake, average daily gain (ADG), and feed conversion ratio (FCR). A total of 16 male rabbits aged three months were used in a completely randomized design consisting of four treatments and four replications. The treatments included P0 (100% pellet), P1 (60% pellet + 40% elephant grass), P2 (60% pellet + 40% Leucaena leucocephala leaves), and P3 (60% pellet + 40% Gliricidia sepium leaves). Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test when significant differences were detected. The results showed that forage type had a significant effect (P<0.05) on feed intake, ADG, and FCR. The highest feed intake was observed in P3 (84.58 g/head/day), while the lowest occurred in P0 (71.29 g/head/day). Similarly, the greatest ADG was recorded in P3 (25.43 g/head/day), compared to the lowest value in P0 (17.87 g/head/day). The best (lowest) FCR was also achieved by P3 (3.33), indicating superior feed utilization efficiency relative to the other treatments. In conclusion, the inclusion of high-quality forages, particularly Gliricidia sepium, improved feed intake, growth rate, and feed efficiency in Rex rabbits. The combination of 60% pellet and 40% Gliricidia leaves (P3) is recommended as the most effective dietary formulation to enhance growth performance under intensive production systems.